Momentum-space signatures of Berry flux monopoles in the Weyl semimetal TaAs - M. Ünzelmann (Nature Portfolio, 2021)
Weyl semimetals exhibit Berry flux monopoles in momentum-space, but direct experimental evidence has remained elusive. Here, the authors reveal topologically non-trivial winding of the orbital-angular-momentum at the Weyl nodes and a chirality-dependent spin-angular-momentum of the Weyl bands, as a direct signature of the Berry flux monopoles in TaAs.